Ultra‐Stable Aqueous Zinc Batteries Enabled by β‐Cyclodextrin: Preferred Zinc Deposition and Suppressed Parasitic Reactions - Meng, Chao; He, Weidong; Jiang, Liwen; Huang, Yuan; Zhang, Jintao; Liu, Hong; Wang, Jian‐Jun (Advanced functional materials, 2022)
The intrinsic zinc dendrite growth aggravated by the uneven electric field at the Zn anode surface and the water‐induced parasitic reactions have largely impeded rechargeable aqueous zinc‐ion batteries for the practical applications in large‐scale energy storage. Here, an effective strategy is proposed to manipulate Zn deposition and simultaneously prevent the generation of insulating by‐products (Zn4SO4(OH)6·xH2O) for improved plating/stripping on Zn anodes by the addition of a nontoxic electrolyte additive, β‐cyclodextrin (β‐CD). The simulation results indicate that β‐CD molecules prefer to adsorb horizontally on Zn (002) plane, regulating the diffusion pathways and deposition sites of Zn2+ for the preferred Zn deposition along (002) plane without dendrite formation and inhibiting the H2 generation and the formation of Zn4SO4(OH)6·xH2O by facilitating desolvation of [Zn(H2O)6]2+. Consequently, an ultra‐long stable cycling up to 1700 h at a high current density of 4 mA cm−2 can be achieved by the addition of β‐CD, 17 times that of the pure ZnSO4 electrolyte and the remarkable stability is also maintained under harsh test condition (40 mA cm−2, 20 mAh cm−2). This study highlights the important role of β‐CD in engineering the interfacial stability during Zn plating/stripping for high‐performing aqueous batteries. β‐Cyclodextrin (β‐CD) additive with a special cavity structure is developed to regulate the deposition orientation of zinc ions and inhibit the parasitic reaction at the same time, resulting in highly reversible and stable Zn anode. Herein, the Zn//Zn cells with β‐CD display remarkable stability at different current densities ranging from 4 to 40 mA cm−2, much better than that in pure ZnSO4 electrolyte. This study demonstrates the remarkable effect of β‐CD on stabilizing the Zn anodes and provides insight into the design of versatile electrolytes for aqueous ion batteries.